Políticas públicas de democratização do ensino superior : um estudo sobre a ocupação das vagas nos cursos de graduação na Universidade Tecnológica Federal do Paraná - Câmpus Francisco Beltrão - Czerniaski, Lizandra Felippi (2014)
This dissertation is a study about the non-occupancy of places in undergraduate courses of the Federal Technological University of Paraná - Francisco Beltrão campus. The research has as a theoretical framework the contributions by the French sociologist Pierre Bourdieu to the field of education. Moreover, it provides an overview about public policies for higher education in Brazil. SISU (Unified Selection System) is shown as the way to enter the undergraduate courses in Federal Public Institutions, replacing the college entrance examination. The policy of quotas is characterized as an opportunity for access to higher education to social and racial minorities, historically excluded from the academic field. From the research problem which is based on the idleness of places in undergraduate courses already mentioned, a field research was conducted; it aimed to identify the reasons why the applicants to the places in university did not enroll in the institution chosen as the locus of this research, providing, this way, continuous idle places. In order to develop the research, questionnaires seeking answers to the non-enrollment were sent through email to the applicants invited to enroll on campus and that did not do it. 1290 questionnaires were sent, of which 80 returned responded and served to analyze the problem that guided this dissertation. The reasons given for not enrolling can be combined in several factors, ranging from geographic distance from campus, through the offerings of more attractive and / or more accessible undergraduate courses in other higher education institutions, to the family of the applicant financial situation.